Amelioration by Catalpol of Atherosclerotic Lesions in Hypercholesterolemic Rabbits - Liu, Jiang-yue; Zhang, Dai-juan (Planta Medica, 2015)
The aim of the present study was to evaluate the effects of catalpol administration on atherosclerosis. Atherogenesis was induced by a high-cholesterol chow in male New Zealand White rabbits that were randomly assigned to receive atorvastatin (5 mg/kg/day), catalpol (5 mg/kg/day), or vehicle by oral gavage for 12 weeks. The rabbits were sacrificed after 12 weeks, and the thoracic aorta and serum were collected for further pathological and molecular biological analysis. Catalpol administration resulted in significantly attenuated atherosclerotic lesions. Total cholesterol, triglycerides, and low-density lipoprotein cholesterol were remarkably reduced, and high-density lipid cholesterol was elevated in the catalpol-treated group. Catalpol reduced the levels of tumor necrosis factor-α, interleukin-6, monocyte chemoattractant protein-1, soluble vascular cell adhesion molecule-1, and soluble intercellular adhesion molecule-1 in the serum, as well as vascular cell adhesion molecule-1, monocyte chemoattractant protein-1, tumor necrosis factor-α protein, inducible nitric oxide synthase, matrix metalloproteinases-9, and nuclear factor-κB protein65 in the aortic arch. In addition, catalpol treatment reduced the lipid peroxidation levels, while elevating antioxidant capacity. Catolpol pretreatment inhibited the nuclear translocation and DNA binding activity of nuclear factor-κB protein in oxygenized low-density lipoprotein-stimulated EA.hy926 cells. Furthermore, catolpol pretreatment activated nuclear factor erythroid 2-related factor 2 and upregulated the expression of its downstream antioxidant enzyme heme oxygenase. In summary, catalpol attenuated atherosclerotic lesions by the inhibition of inflammatory cytokines and oxidative stress status in a rabbit atherosclerotic model and enhanced the antioxidant capacity in oxygenized low-density lipoprotein-stimulated EA.hy926 cells. These results suggest that catalpol may be used to prevent and attenuate atherosclerosis.
Keywords: atherosclerosis; catalpol; inflammatory cytokine; oxidation; Nrf2